One-year outcomes of rosuvastatin versus placebo in sepsis-associated acute respiratory distress syndrome: prospective follow-up of SAILS randomised trial. Issue 5 (2nd March 2016) - Dinglas, Victor D; Hopkins, Ramona O; Wozniak, Amy W; Hough, Catherine L; Morris, Peter E; Jackson, James C; Mendez-Tellez, Pedro A; Bienvenu, O Joseph; Ely, E Wesley; Colantuoni, Elizabeth; Needham, Dale M
Abstract : Background: Prior randomised trials have evaluated statins in patients with sepsis and acute respiratory distress syndrome (ARDS), but there has been no comprehensive evaluation of long-term effects, despite potential neuromuscular and mental health adverse effects of these drugs. Aim: To evaluate the effect of rosuvastatin versus placebo on survival, physical function and performance, and mental health outcomes in patients with sepsis-associated ARDS. Methods: Prospective follow-up evaluation of the ARDS Clinical Trials Network Statins for Acutely Injured Lungs from Sepsis trial of rosuvastatin versus placebo in 568 mechanically ventilated patients with sepsis-associated ARDS, with blinded 6-month outcome assessment performed in the 272 eligible survivors for age-adjusted and sex-adjusted 36-Item Short Form Health Survey (SF-36) physical function and mental health domains, and in 84 eligible survivors for the 6 min walk test, along with secondary outcomes evaluations of survival, and additional patient-reported and performance-based measures at 6-month and 12-month follow-up. Results: Over 1-year follow-up, there was no significant difference in cumulative survival in the rosuvastatin versus placebo groups (58% vs 61%; p=0.377), with survivors demonstrating substantial impairments in physical function and mental health. Rosuvastatin versus placebo had no effect (mean treatment effect (95% CI)) on SF-36 physical function (0 (−7 to 8), p=0.939) or mental health (−6 (−12 to 1) p=0.085) domains, 6 min walk distance (per cent predicted: 2 (−9 to 14), p=0.679) or the vast majority of secondary outcomes. Conclusions: Over 1-year follow-up, patients with sepsis-associated ARDS had high cumulative mortality, with survivors commonly experiencing impairments in physical functioning and performance, and mental health. Randomisation to rosuvastatin had no effect on these outcomes. Trial registration number: NCT00979121 and NCT00719446 .